The Association of Electrolytes, Trace Elements, and Vitamin C with Kidney Function in Iraqi Celiac Patients - Adel, Tabarak; Karim, Nada Abdel (Iraqi Journal of Science, 2025)
Celiac disease is a chronic autoimmune disorder that occurs in genetically predisposed individuals who consume gluten-containing grains, such as wheat, barley, and rye, triggering a gradual immune response that damages the small intestine and can also affect other organs. Accurate biochemical markers are essential for diagnosis, risk assessment, and the implementation of effective treatments to enhance clinical outcomes. This study aimed to evaluate changes in blood levels of urea, creatinine, electrolytes (sodium, potassium, and chloride), trace elements (magnesium and zinc), and vitamin C in Iraqi individuals diagnosed with celiac disease. A total of 100 patients with celiac disease who were not following a gluten-free diet were compared to 57 healthy controls. The results showed a significant increase in serum urea and creatinine levels (p < 0.05), while electrolyte levels remained unchanged. Conversely, trace element levels of (magnesium and zinc), and serum vitamin C levels were significantly decreased in both Patients female (PI) and Patients male (PII) compared to their respective healthy groups control female (CI) and control male (CII). These findings suggest that the observed variations may be linked to an increased risk of renal dysfunction due to elevated serum urea and creatinine levels in individuals with celiac disease.